Análise dos alelos variantes de RHD e RHCE em pacientes aloimunizados e doadores de sangue com expressão alterada do antígeno RhD - Silva, Thamy Caroline de Souza [UNIFESP] (2019)
Background: The Rh system is considered the largest and most polymorphic blood group system, consisting of more than 50 antigens. The existence of a large number of RH alleles results in variant phenotypes that often complicates the blood phenotyping and the distinction between auto and alloantibodies in recipients who have antibodies in the presence of the corresponding antigen. To make blood transfusion safer, it is necessary to know these variants. Aims: To identify the RHD and RHCE variant alleles present in patients who produce anti-Rh antibodies in the presence of corresponding Rh antigen and to detect variant alleles in blood donors with weak reactivity of RhD antigen in serological phenotyping. Methods: Samples of 48 blood donors with serological reactivity in RhD typing of up to 3+ (on a scale of 0 to 4+) and samples from 29 patients who had anti-Rh antibody in the presence of the corresponding Rh antigen were evaluated molecularly for RHD and RHCE alleles using the blood-MLPA assay (Multiplex Ligation-dependent Probe Amplification) and Sanger sequencing. Results: We found mutation in 45 blood donors, 24/45 (53%) were weak RhD, 2/45 (4%) partial RhD, 19/45 (42%) weak and partial RhD and the remaining 3/48 (6%) did not present mutation in the RHD allele, but are in cis with RHCE*Ce. In patients, 12/29 with anti-e only 4 presented genotypes that predicted partial e-antigen; 11/29 presented anti-D, 6 were identified as partial D; 2/29 presented anti-c and one was identified as c-partial antigen; 4/29 with anti-E and 4/29 with anti-C showed no mutations in RHCE. Conclusions: Through the low serological reactivity of RhD typing in blood donors we can find individuals with altered RH genotypes that are clinically important. When the antibody is found concomitantly with the corresponding antigen, the serological distinction between auto and alloantibody is complex, in these cases the molecular methods may support the detection of possible RH variant alleles.